Heritage studies and measured drawings of Masjid Jamek Sultan Abdul Samad, Kuala Lumpur - Abdul Rahim, Asiah; Hj Mohd Ariffin, Noor Aziah; Azmin, Aida Kesuma; Sanusi, Aliyah Nur Zafirah; Asif, Nayeem; Mohd Nazri, Anis Husna; Nge Kyaw, Ei Nge; Mohamad Yusuf, Fatin Nabilah; Suhaimi, Hanis Najeha; Muhammad, Maizan Azmatun; Nik Mohd Shaharil, Nik Anis Sabrina; Zbair, Nour Elhoda; et al. (2020)
Masjid Jamek Sultan Abdul Samad was built in 1909 following the demolition of Masjid Kampung Rawa that is located at Java Street (Jalan Tun Perak) due to expansion of road and to carter the increasing number of Jemaah. The masjid was one of the earliest mosques in Kuala Lumpur. The establishment of Kuala Lumpur is always closely related to Masjid Jamek Sultan Abdul Samad. Furthermore, the quaint masjid is located at the confluence of Klang River and Gombak River, which gives Kuala Lumpur its name. The masjid has gone through a few renovations to cater for the needs of the worshippers. Besides, to pay respect to the third Sultan of Selangor, Almarhum Sultan Abdul Samad, the masjid has been renamed from Masjid Jamek Kuala Lumpur to its current name, Masjid Jamek Sultan Abdul Samad. This report material is separated into (two) 2 parts. The first part of the report highlights the literature review and the findings of Masjid Jamek Sultan Abdul Samad from the fieldwork. It focusses on the contextual studies, the colonial influences, the background history, the details of building construction and case studies from buildings with similar architectural elements. Meanwhile, the second part of this report comprise a compilation of measured drawings of Masjid Jamek Sultan Abdul Samad in 2D and 3D. This report is to convey the analytical studies of the part of Masjid Jamek history and chronology, architectural influences, and the site context of the masjid, and how the structure affect the surrounding context, the culture, the society and the economy activities of Kuala Lumpur until this day. Hopefully, these studies can be beneficial and better enhancement to others in term of its architectural and historical data. Therefore, it is important for the next generation to come appreciate the past story amid the rapid growth and advancement of Kuala Lumpur.